Knowledge and Practice of Laptop Ergonomics in Office Employees - Batool Fatima, Umema Mumtaz, Sara Zulfiqar, Sameera Mushtaq, Rafia Imtiaz, Muhammad Adnan Khan, Sumbal Saleem, Kanwal Fatima, Hira Rafique, Intsam Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The rapid growth of information technology has led to increased laptop usage in offices, industries, and educational settings. However, the lack of knowledge and practice of ergonomics during laptop use can result in musculoskeletal discomfort and constrained postures. It is important to provide information to frequent laptop users about the ergonomics effects to prevent musculoskeletal disorders. Objective: Study is aimed to access knowledge and practice level of laptop ergonomics among office employees. Methodology: The following descriptive study was conducted on a sample size of 195 employees calculated through Rao-soft software. Data was collected by using convenient sampling technique from two private and one government office setting operating in Lahore, Pakistan, using a questionnaire assessing knowledge and practice of laptop ergonomics among office employees. Employees fulfilling the eligibility criteria were encouraged to fill the questionnaire after informed consent. Result: 195 employees with mean age 29.892±8.008 participated in this study. 75.9% had fair knowledge of laptop ergonomics and 59.6% employees practice this moderately. 12.3% participant had good knowledge of laptop ergonomics out which only 7.2% have good practice of laptop ergonomics while 11.8% population had poor knowledge and 33.3% had poor laptop ergonomic practice. Conclusion: More than half of the office employees are well known with knowledge of laptop practice but they don’t practice ergonomics in daily work routine. Workplace administrations should design offices based on ergonomic principles to prevent musculoskeletal disorders. Education programs and seminars on laptop ergonomics can raise awareness among employees. Keywords: Knowledge and practice, laptop ergonomics, office employees